Rekognisi Axel Honneth: Gramatika Moral Bagi Defisit Rasionalitas Beragama - Meitikasari, Diah; Drianus, Oktarizal (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2021)
This paper aims to explore Axel Honneth's thoughts on recognition. This is considered important that today, religious moderation is expected to be a mode of living together that able to reconstructs a just and rational moral grammar, instead of falling into a deficit of rationality. This paper uses a literature study approach with the main source of Honneth's work, The Struggle for Recognition: Moral Grammar for Social Conflict. Several points were learned, namely: 1) recognition for Honneth is a normative basis for recognition and social struggle that eliminates all forms of disrespect; 2) Honneth's Recognition manifests in three domains: love, rights, and solidarity; 3) Mutual relations in three domains which are basic self-confidence, self-respect, and self-esteem; 4) Honneth's recognition can be a moral grammar for religious moderation efforts in Indonesia.